A Conceptual Model of Buddhist Chief Executive Officer (BCEO) for the Modern World - Thongpool, Patsakpol; Mahatthanadull, Sanu (Journal of International Buddhist Studies, 2021)
This article aims to explore the conceptual model of the Buddhist Chief Executive Officer (BCEO) for the modern world. The senior executives can apply to use for more benefit and more effective in the new world. The concept of senior management in Theravada Buddhism is another approach that can help senior executives to use it as a guideline for organization management. The four types of executives to be BCEOs are follow: 1) Founder Type, 2) Appointed Leader Type, 3) King Type, and 4) Merchant Type. BCEO types divided into family and non-family types. The physical characters of a BCEO should be good traits such as a straight body, a smiling face, a beautiful voice and all good resounding appearance. The mental characters of the BCEO should have the emotional intelligence, social responsibility, good management and decision-making skills. The BCEO should possess the virtues of Dhamma, which are the four keys to success, namely 1) Pāpaṇika-dhamma, 2) Aparihāniya Dhamma, 3) Dasavidha-rājadhamma and 4) Kalyāna-mitra. The personal qualities of the BCEO are: 1) Being practiced perfection Pāramī, 2) Achieving higher knowledge or Abhiññā and 3) Being steadfast in Dhamma. The required qualifications of a BCEO are a leadership style, education level, professionalism and experienced. The conceptual model of the Buddhist Chief Executive Officer (BCEO) is useful to apply for organizations in the modern world.